Chinese Indonesians in Post-Suharto Indonesia 2018
DOI: 10.5790/hongkong/9789888455997.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Politics and the Chinese in Post-Suharto Indonesia

Abstract: This chapter focuses on the involvement of Chinese Indonesians in electoral politics in post-Suharto Medan and Surabaya and how this intersects with their stereotypical position as businesspeople. The opening up of a democratic environment in post-Suharto Indonesia has prompted many Chinese Indonesians to get involved in electoral politics. Some of them become electoral candidates in order to push for reform and positive changes in Indonesia and reject approaches of support for their campaigns in return for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In other words, the cultural values taught from generation to generation in the Baduy tribe in terms of forest management and good for the environment are still being done. What is done by the Baduy community is in line with the understanding conveyed by Giddens that the relationship between aspects is one way of forming a process that can create a culture or pattern of behavior called habitus by Bourdieu (Chong, 2015).…”
Section: Sustainable Forest Management In the Baduymentioning
confidence: 55%
“…In other words, the cultural values taught from generation to generation in the Baduy tribe in terms of forest management and good for the environment are still being done. What is done by the Baduy community is in line with the understanding conveyed by Giddens that the relationship between aspects is one way of forming a process that can create a culture or pattern of behavior called habitus by Bourdieu (Chong, 2015).…”
Section: Sustainable Forest Management In the Baduymentioning
confidence: 55%
“…4 For instance, in 1999, a court dispute was filed between a former committee member and the CCCB and in 2013, the Registrar of Societies ordered CCCB to freeze its activities due to unresolved internal issues related to the lack of transparency in committee election. 5 The use of Chinese associations to serve the leader's personal interests is not peculiar to Brunei (see Hoon, 2008 for the Indonesian case as an example).…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“… The use of Chinese associations to serve the leader's personal interests is not peculiar to Brunei (see Hoon, 2008 for the Indonesian case as an example). …”
mentioning
confidence: 99%
“…Subsequent studies into Chinese Indonesians were generally conducted using the perspective of political studies and focused more on the ways Chinese Indonesians were involved in national-level political tensions (Chen, 2022;Pearson, 2008). Previous studies have also revealed the business and social-economic privilege of the Chinese Indonesians (Chong, 2015;Efferin & Pontjoharyo, 2006;Koning, 2007). This combination of political tension and social-economic privilege puts the Chinese Indonesians in a position that does not fit with the pattern of minority groups in BAME/BIPOC studies in the Global North who are both disadvantaged racially and economically (Pols & Suci, 2021).…”
Section: Introductionmentioning
confidence: 99%